Gambaran kesiapsiagaan siswa SMA Lokon St. Nikolaus Tomohon terhadap bencana erupsi gunung berapi - Adrian Jonathan Angir; Windy Mariane Virenia Wariki; Dina Victoria Rombot (JURNAL KEDOKTERAN KOMUNITAS DAN TROPIK, 2022)
Volcanic eruptions can cause health problems. To prepare for a volcanic eruption disaster, knowledge, attitudes, and actions are needed which are important components of preparedness. This study aims to describe the preparedness of Lokon St. Nikolaus Tomohon highschool students on the eruption of Mount Lokon. This research is descriptive in nature with a cross-sectional research design which was carried out in October-December 2022. This study used a simple random sampling method and obtained 173 respondents who met the inclusion and exclusion criteria. The instrument used was a student preparedness questionnaire for volcanic eruptions. The level of preparedness of Lokon St. Nikolaus Tomohon in the good category totaling 152 students (87.9%), based on age characteristics in the good category there are 19 years old with a total of 2 students (100%), based on gender characteristics in the good category there is female gender totaling 90 students (90.9 %), and based on the characteristics of the region of origin in the good category, there are other regions with a total of 55 students (90.2%). Keywords: preparedness, volcanic eruption